Collège Glendon College. Mission et démissions dans la création identitaire d’une institution collégiale nationale - Roy, Sandra (Revue YOUR Review (York Online Undergraduate Research), 2022)
Glendon College (Toronto, Canada) was founded in 1966 as a college providing bilingual liberal-arts education. The first two administrations, between 1966 and 1976, shaped the college and imposed on it the foundations on which it is still based. Using documents produced by the administration, faculty, and students, as well as interviews with college employees, the evolution of Glendon’s descriptors over these 10 years is examined with the goal of outlining how the college was defined. It is proposed that the identity of Glendon is constantly questioned due to the confrontation between dreams and realities. If the college is small physically, in its student body and in terms of faculty, its administrators saw big. They dreamt of a bilingual national college training new citizens interested in the contemporary problems of the country. The size of Glendon and its ethos bucked the trends in education at the time, which aimed towards multiversity and specialized training. Finally, the desire to provide an environment and a bilingual education faced structural problems and created tensions with students. If Glendon survived these first 10 years, it is because its two first principals knew how to adapt their dreams of grandeur to the reality of their means, at the price of a constant, and at times tumultuous, redefinition of identity. The study of Glendon’s heritage helps to better understand the problems facing the college today.